KEABSAHAN KUITANSI SEBAGAI BUKTI JUAL BELI TANAH MENURUT HUKUM TANAH NASIONAL : Validity of Receipt As Proof of Land Sale According To the National Land Law - Maliha, Elvia Qonitah; Keumala, Dinda (AMICUS CURIAE, 2024)
According to the National Land Law, the act of buying and selling land must meet the characteristics of clear, cash-based, and genuine transactions. The issue addressed in this research is the validity of land transactions conducted with receipt evidence, as per the National Land Law and the District Court Decision Number 191/Pdt.G/2021/PN Smg, and how to register the transfer of rights when the seller's whereabouts are unknown, also related to the aforementioned court decision. This study adopts a normative research approach with descriptive analysis. Secondary data obtained from literature studies are utilized, complemented by primary data to support the arguments. The research employs a qualitative analysis method, and conclusions are drawn using the deductive approach. It should be noted that a land transaction conducted solely with a receipt as evidence, without a Sale and Purchase Deed executed before a Land Deed Making Official, cannot be deemed valid according to the National Land Law, as it fails to fulfill the clear transaction nature and the formal requirements of buying and selling.